MM Íslandskort. Ísland, fjórðungskort 1:300 000 / kortagerð--Hans H. Hansen = Iceland / cartography--Hans H. Hansen - Mál og menning (Mál og menning, 2004)
Norðausturland : NA-land = Northeast -- Norðvesturland : NV-land = Northwest -- Suðausturland : SA-land = Southeast -- Suðvesturland : SV-land = Southwest. Road map with tourist features.; Panel title.; Ed. statements at foot of legend, e.g.: Fyrsta útgáfa = First edition -- þriðja útgáfa = Third edition; and on title panel, e.g.: 2000 2 -- 2000 3.; Various eds. of some sheets.; Coverage complete in 4 sheets.; Text, distance table, and col. ill. on verso. Text, legend, and panel title in Icelandic, English, German, and French. Color; 1:300,000